Development of powerpoint-based learning media to improve student learning outcomes on the material of economic science concepts at MA Hamid Rusydi Malang - Rochanahh, Siti; Aji, Sudi Dul; Ni’matullah, Onik Farida; Kusufa, Roni Alim Ba’diya (Penelitian Ilmu Pengetahuan Sosial, 2024)
Introduction: Learning resources are an important component of learning. The purpose of this study is to analyze the feasibility, viability, effectiveness, or extent of development of PowerPoint-based learning resources on the topic of conceptual economics in MA Hamid Rasidi Malang. Methods: The research methodology was developed using two types of data, quantitative and qualitative. Finding: The development of this learning tool was adapted from the development model of Borg and Gall (2003), which has 10 phases, but the researchers implemented eight phases due to time, energy, and cost implications. The eight phases are: research and data collection, planning, product format development, initial testing, product revision, intensive field testing, final product revision, implementation, and deployment. The study found that based on feasibility testing by six reviewers, the validity level of the learning media product averaged 96% high feasibility from two subject matter experts, 97% high feasibility from two language experts, 91% high feasibility from two media experts, two social studies teachers. The average feasibility was 96% high from MA. Hamid Rasidi Malang and MA. Said Malang, and 91% high from the students of MA. Hamid Rasidi Malang and MA. Nasional Malang. Conclusion: Malang students indicated that the initial test results before the use of the PowerPoint-based materials were highly effective with an average of 92%, and the results after the use of the PowerPoint-based materials were highly effective with an average of 98%. This indicates that the developed product can be used in social studies and is practical and effective.